Design and implementation of an electrochemical sensor, based on a microfluidic system, to determine acetaminophen concentrations in water (2022)
In order to address water quality control difficulties in remote locations, an electrochemical sensor is designed, manufactured and characterized to detect acetaminophen on aqueous solutions. CAD (Shapr3D) and PCB (Altium Designer) software tools were used in the design of the sensing electrodes. The characterization of the sensor was done by exposing the electrode to acetaminophen diluted in purified water and then measured the change in the output electrical signal through cyclic voltammetry.